PEMBERDAYAAN MASYARAKAT MELALUI PENGUATAN KELEMBAGAAN DALAM MEWUJUDKAN PEMBANGUNAN PERIKANAN (STUDI KASUS DESA KAMBITIN DAN KAMBITIN RAYA KECAMATAN TANJUNG) - Murjani, STIA Tabalong (Jurnal PubBis, 2017)
Local fish hatchery units (UPRs) located in Kambitin and Kambitin Raya Villages of Tanjung District are the development centers of the aquacultures in Tabalong Regency. In order to support the productivity of those FHUs, the local government established a fish breeding center. The breeding center covers and supervises eight FHUs (Sido Makmur, Usaha Bersama, Harapan Makmur, Karya Makmur, Jaya Mukti, Barokah Jaya, Bumi Makmur and Sri Lestari). The study was aimed to analize the corcodance between the UPRs and the fish breeding center in Kambitin and also to analyze the local government intervention in the framework of community empowerment through strengthening institution to support fishery development. The result of this research showed that was a competition and conducive situation between the fish breeding center and the fish hatchery unit. This situation was a negative effect of the implementation of Regional Regulation (PD No. 05 Year 2006) about retribution of the local goverment?s product unit and regulation of Regents Tabalong (Perbup No. 02 Year 2008) about the implementation directions of the regional regulation. Due to that regulation, the original function of the fish breeding center, as supervising unit of UPRs, was changed to be one the income generating units of the local government. Consequently, the fish breeding center with a good productivity became a new competitor for the UPRs with lower competitiveness. In addition, the relationship among them was not conducive. Therefore, a strategic policy of the local government to reset the role of the fish breeding center to its original function should be taken to stabilize their relationship. In addition, the fish breeding center, the fish should be prohibited to market its products to the same consumers of the UPRs. Inclusion, as an effort to empower the community, intervertion of the local government is required by strengthening the local institutions such as UPRs and the fish breeding center proportionally. Keywords   :    Community Empowerment, Institutin Strangthening, Government Intervention.